Implementasi Kebijakan Dalam Pemberian Bantuan Stimulus Ekonomi Kepada Usaha Mikro Kecil Dimasa Pandemik Covid-19 Pada Dinas Perindustrian Dan Perdagangan Provinsi Sumatera Utara - Muhammad Anshary; Heri Kusmanto; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this paper is to find out the implementation and the factors that influence the implementation of policies in providing economic stimulus assistance to micro and small businesses during the Covid-19 pandemic at the Industry and Trade Office of North Sumatra Province. The research method used in this study is a qualitative descriptive research method. In order to approach this problem, the theory from G.C. Edwards III is used. The results of the study stated that communication on the implementation of policies in the provision of assistance was still not carried out optimally and effectively. Resources in the implementation of policies in the provision of assistance are still not implemented optimally. The disposition of the policy implementation in the provision of assistance is considered to have been carried out effectively and optimally. The bureaucratic structure in the implementation of policies in the provision of assistance is considered not to have been implemented effectively and optimally. Communication factors in the implementation of policies in the provision of assistance there are still obstacles. Factors Resources in the implementation of policies in the provision of this assistance there are still obstacles. The disposition factor in the implementation of the policy in the provision of assistance is considered one of the supporting factors for the implementation of the policy. Bureaucratic Structure Factors in the implementation of policies in the provision of assistance there are still obstacles. The factor of fragmentation (division of tasks), it was found that there was still an incompatibility of the division of tasks that had been determined, with the process of implementing policies in the field.